The Effect of Service Quality and Price on Customer Loyalty Mediated by Customer Satisfaction at PT Indosat Ooredoo Hutchison in South Jakarta - Rizka Rahmadina; Budi Prasetiyo (CV. Creative Tugu Pena, 2026)
This research seeks to examine the influence of service quality and pricing on customer loyalty, while considering customer satisfaction as a mediating variable among prepaid users of PT Indosat Ooredoo Hutchison in South Jakarta. The study is motivated by a decline in the number of customers as well as fluctuating perceptions regarding service quality and pricing, which are assumed to impact customer loyalty. A quantitative research design was applied using a survey method, where data were gathered through questionnaires distributed to prepaid Indosat users. The analysis was conducted using Structural Equation Modeling with a Partial Least Squares (PLS-SEM) approach. The findings reveal that both service quality and price significantly and positively affect customer satisfaction. In addition, customer satisfaction is proven to have a significant positive impact on customer loyalty. Service quality and price also directly influence customer loyalty. Moreover, customer satisfaction is found to act as a significant mediating variable that strengthens the relationship between service quality, price, and customer loyalty. These results suggest that enhancing service quality and implementing pricing strategies that align with customers’ perceived value are essential for increasing both customer satisfaction and loyalty.